2020
DOI: 10.3390/w12102760
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint Management for Sustainable Growth in the Bangladesh Apparel Sector

Abstract: Bangladesh is one of the fastest growing economies in the world, primarily driven by its textile industries. A high amount of water is consumed and polluted in the production and processing of raw material to the final product in the textile industry. Therefore, water footprint assessment is important for textile products. In this study, the water footprint of cotton cultivation, transportation and textile industry was calculated by analyzing the amount of imported cotton, production and processing capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…Residues with high salinity or acidic/basic pH however, would need more thorough treatment. 103 Please do not adjust margins Please do not adjust margins Table 2: Comparison of dye production processes. Process steps and chemicals involved show great potential for sustainability of manufacturing processes based on fermentation.…”
Section: Bioproduction Of 'Critical' Synthetic Dye Alternativesmentioning
confidence: 99%
“…Residues with high salinity or acidic/basic pH however, would need more thorough treatment. 103 Please do not adjust margins Please do not adjust margins Table 2: Comparison of dye production processes. Process steps and chemicals involved show great potential for sustainability of manufacturing processes based on fermentation.…”
Section: Bioproduction Of 'Critical' Synthetic Dye Alternativesmentioning
confidence: 99%
“…Dyeing is one of the major contributors to pollution as shown in Figure 1 (Hossain & Khan, 2020). These processes involve colouring fibres, yarns, fabrics or clothes, and giving wet treatments to enhance the appearance, hand, and performance.…”
Section: Water Pollutionmentioning
confidence: 99%
“…[ 107 ] For example, a study found that between 2012 to 2016, the annual water footprint in the Bangladesh textile industry was found to be ≈1.8 billion cubic meters. [ 108 ] Additionally, the textiles industry emitted ≈1.75 billion CO 2 e (carbon dioxide equivalent) tons globally in 2015, [ 106 ] an estimated 8.1% [ 109 ] to 10% [ 110 ] of total global GHG emission. In general, the production of nonwoven fabric involves less water consumption and similarly, less water is needed for single‐use PPE during their usage.…”
Section: The Environmental Footprints Of Protective Clothingmentioning
confidence: 99%